Children's time: Childhood, aesthetics and politics in benjamin - Sanches, Eduardo Oliveira; Ramos, Estéfani Dutra [UNESP]; da Silva, Divino José [UNESP] (FapUNIFESP (SciELO), 2020)
In his writings on modernity, technique and technical reproducibil-ity, Benjamin proposes a theoretical view of reproducible art that dialogues with the demands of the new temporality. If the modes of artistic production are expanded by technological advances, resizing their field of action to more modern forms of expression such as radio, for example, there is here a new experimental relationship between the public and the work, in addition to a new intermediary function. The concern with the use of technique for totalitarian purposes, however, made the author formulate the demand for a politicization of art. This politicization is present in his radio work with children that is linked to the commitment to use the apparatus for enlightenment.
A hora das crianças: Infância, estética e política em benjamin
Keywords: Childhood; Enlightenment; Politics; Radio; Technical Reproducibility